RELEVANSI TRADISI NGEMBLOK DI DESA MENTORO DENGAN KONSEP KHITBAH DALAM KITAB FATHUL QORIB - Farichatul Aula Nikmatur Rohmah; masrokhin (LPPM Universitas Bina Insan, 2026)
The Ngemblok tradition in Mentoro Village, Tuban Regency, represents a distinctive marriage proposal practice in which the proposal is initiated by the woman's family, differing from the commonly practiced khitbah tradition in Muslim society. This study aims to analyze the implementation of the Ngemblok tradition and examine its relevance to the concept of khitbah as presented in Fathul Qorib and within the broader framework of Islamic law. The research employed a qualitative method with a socio-juridical approach through a field case study. Unlike previous studies, which generally discuss khitbah or local marriage customs separately, this research specifically examines the interaction between the Ngemblok tradition and the Shafi'i jurisprudential perspective articulated in Fathul Qorib. The findings indicate that the Ngemblok tradition is conducted through family deliberation and with the involvement of community leaders to preserve social propriety and communal acceptance. An analysis of Fathul Qorib reveals that although khitbah is described as a proposal initiated by a man, the text does not explicitly prohibit women from initiating a marriage proposal. Based on these findings, the Ngemblok tradition can be understood as a customary practice that is compatible with the principles of Islamic law, provided that it does not contradict the provisions of the Sharia. This study contributes to the literature by demonstrating how local customary practices can be interpreted within the framework of classical Islamic jurisprudence, thereby enriching scholarly discussions on the relationship between Islamic law and local culture in marriage practices.